1999
DOI: 10.1021/jp9914929
|View full text |Cite
|
Sign up to set email alerts
|

Application of One-Dimensional Dipolar Shift Solid-State NMR Spectroscopy To Study the Backbone Conformation of Membrane-Associated Peptides in Phospholipid Bilayers

Abstract: A simple one-dimensional dipolar shift solid-state NMR experiment is demonstrated to study the backbone conformation of membrane-associated peptides embedded in phospholipid bilayers. The nitrogen-15 chemical shift and 1 H-15 N dipolar coupling parameters are measured on a magainin peptide selectively labeled with a 15 N isotope at the Gly-18 site. Fully hydrated multilamellar vesicles and uniaxially oriented bilayer samples are used to determine the orientation of the peptide plane relative to the direction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 60 publications
5
30
0
Order By: Relevance
“…A 1-D dipolar-shift powder pattern, shown in Figure 3D, was used to determine the orientation of the chemical shielding tensor relative to the 15 N-labeled residues in magainin and pardaxin (42,43,50). The line shape depends strongly on the strength of the dipolar coupling and the angle so these parameters are determined precisely with this method, but R cannot be determined as precisely because the line shape varies only slightly with R for small values of , as is the case here (42,43). These parameters, determined from the solid powder spectra, were used to interpret the spectra of LL-37-L in oriented lipid bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…A 1-D dipolar-shift powder pattern, shown in Figure 3D, was used to determine the orientation of the chemical shielding tensor relative to the 15 N-labeled residues in magainin and pardaxin (42,43,50). The line shape depends strongly on the strength of the dipolar coupling and the angle so these parameters are determined precisely with this method, but R cannot be determined as precisely because the line shape varies only slightly with R for small values of , as is the case here (42,43). These parameters, determined from the solid powder spectra, were used to interpret the spectra of LL-37-L in oriented lipid bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…A variable temperature solid-state 15 N NMR study on lipid vesicles containing magainin 2 revealed its backbone dynamics [352]. The backbone dynamics of a channel-forming second-transmembrane segment of GABA receptor in lipid bilayers has been determined using PISEMA experiments [353].…”
Section: Insights Into Biological Problemsmentioning
confidence: 99%
“…For example, it is difficult to establish an experimental condition that efficiently transfers magnetization from protons to carbons (or other low sensitive nuclei) at all sites of a molecule, and also for all molecules, in a bicelle sample. A short contact time crosspolarization (CP) [10] sequence is more efficient for rigid parts of a molecule than for mobile regions, as heteronuclear dipolar couplings in the latter case are averaged by the motion [11,12]. On the other hand, a long contact time or the NOE (nuclear Overhauser effect)-type magnetization transfer may be better for mobile sites of a molecule [13].…”
Section: Introductionmentioning
confidence: 99%